Multidimensional analysis of frailty in older people of a Brazilian community: a cross-sectional study (Research, Society and Development, 2022)
In Brazil, the aging process takes place under unfavorable economic, social and health conditions. Therefore, a better understanding of the functionality patterns of different elderly populations becomes essential, especially in times of Covid-19. The objective of study is to assess the functionality of institutionalized and community older people. Cross-sectional study with 51 older people, divided into two groups: Institutionalized Older People Group (GII) and Community Older People Group (GIC), assessed by the Mini Mental State Examination, Clinical Functional Vulnerability Index-20 (IVCF-20), Barthel Scale, Lawton Scale and Tinneti Scale, descriptive analysis, multivariate multiple correspondence technique, multinomial and binomial logistic regression, with the R software were performed. The results showed: the quartiles: robust GIC (IVCF-20=6.75), independent (Lawton=21/Barthel=100). The fragile GII (IVCF-20=18), partially dependent (Lawton=13/Barthel=100). In GII association of frail older people and high risk of falls. In the GIC there is no association. The GIC showed more chances compared to the GII: 198.34 cognitively normal; 5.48 robust; more than 100,000 independents; and 14 low risk of falls. In this way, it is concluded that older people in the community have better functional performance than older people living in the two Long Term Care Institutions.